Argentine Immigration Policy: A View from Historical Institutionalism - Norambuena-Carrasco, C; Matamoros-Ortiz, R (UNIV ARTURO PRAT, 2016)
This article analyzes the Argentine immigration policy from the perspective of historical institutionalism theory. In the twentieth century, in particular since the enactment of the Residency Law of 1902, that policy was characterized by a restrictive character, which was intensified along the century by different regulations, with Videla Law (1981) as one of its major milestones. With the return of democracy, various projects intended to abolish this law, but it was not until 2004 that this purpose was achieved with the so-called Project Giustiniani. This paper presents a case study of the Argentine immigration policy, supporting the hypothesis that the Immigration Law N degrees 25.871 of 2004 meant the breakdown of Path Dependence followed by the Argentine immigration institutions over the twentieth century.